3 Transforming Graphs Flashcards
From y= f(x)
To y= f(a x)
Stretch in x direction factor 1/a
From y= f(x)
To y =a f(x)
Stretch in y direction factor a
From y= f(x)
To y= f(x) + a
Translation ( 0/a)
From y= f(x)
To y= f( x+ a)
Translation (-a /0)
Form Y = 2^x
To y = 2^4x
Stretching factor 1/4 in x direction
How to make y = x^2 +3x translated by (-2 /0)
X is replaced by (x +2)
(X +2)^2 + 3(x + 2)
X^2 + 7x +10
If f(x) = x^3 - x
Then what does f(2x) =
Stretch factor 1/2 in x direction
And (2x)^3 - (2x) = 8x^3 -2x
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To y = f(x) +a
Translation (0/a)
Y replaced by (y-a)
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To y= f(x-a)
Translation (a/0)
X replaced by (x -a)
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To y = f(x + a)
Translation (-a/0)
Replace x with (x+a)
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To Y = kf(x)
Stretch factor K in y direction
Y is replaced by (1/k)y
(What do you tra./stre. By and what do you replace what with) From y= f(x) To f(1/k)x
Stretch factor 1/k in x direction
X is replaced (1/k)x
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To y=f(kx)
Stretch factor 1/k in x direction
X is replaced by (kx)
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To y= -f(x)
Reflection in x axis
Y is replaced by -y
(What do you tra./stre. By and what do you replace what with)
From y= f(x)
To y=f(-x)
Reflection in y axis
X is replaced by -x
Y=x^2
Stretch factor 3 in y direction, translation (2/0)
Y =3x^2
Y=3(x-2)^2
Y =f(x)stretch factor 1/2 in x direction
Stretch factor 5 in y direction
y =f(2x)
Y = 5f(2x)
Y = 3 x 2^-x
To y= 2^x
Reflection in y axis, stretch factor 3 in y direction
Y = f(x)
To y= 2f (x+1)
Translation (-1/0)
Stretch in y direction factor 2
When does the order in which you carry out transformations matter
Sometimes when both transformations are to the x or both to the y
Y =f(x)
To. Y= f(3x-1)
Translation (1/0) THEN stretch factor 1/3 in x direction
Y =x^3 to y= (3-x)^3
Translation (-3/0) reflection in y axis